PdCu alloy nanocluster and application thereof in catalysis of Suzuki-Miyaura coupling reaction

By preparing and supporting PdCu alloy nanocluster catalysts, the problem of high dosage of precious metal Pd and difficulty in catalyst preparation is solved, and economic cost reduction and catalytic performance improvement are achieved, especially in the Suzuki-Miyaura reaction, which exhibits excellent C-Br bonds. activation ability.

CN119331027AActive Publication Date: 2025-01-21ANHUI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411502606.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-21
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

In the prior art, the amount of precious metal Pd is used is high and the economic cost is high, and the supported catalysts are difficult to synthesis and preparation.

Method used

PdCu alloy nanoclusters, specifically Pd2Cu2(S-Adm)1(DPPM)3 and Pd2Cu2(C7H5F3S)6(DPPF)2, are used, prepared through a one-pot reduction reaction and crystallization method, and loaded on carbon nanotubes to form a catalyst.

Benefits of technology

It effectively reduces the amount of precious metal Pd, reduces the economic cost of the catalyst, and improves catalytic performance and durability. It especially shows better C-Br bond activation ability in the Suzuki-Miyaura coupling reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331027A_ABST
    Figure CN119331027A_ABST
Patent Text Reader

Abstract

The invention discloses a PdCu alloy nanocluster and application of the PdCu alloy nanocluster in catalysis of a Suzuki-Miyaura coupling reaction, and belongs to the technical field of nano materials. The chemical formula of the PdCu alloy nanocluster is Pd2Cu2 (S-Adm) 1 (DPPM) 3, S-Adm represents adamantanethiol, DPPM represents bis (diphenylphosphino-methane), and the chemical formula of the PdCu alloy nanocluster is Pd2Cu2-1. The chemical formula of the PdCu alloy nanocluster is Pd2Cu2 (C7H5F3S) 6 (DPPF) 2, or the chemical formula of the PdCu alloy nanocluster is Pd2Cu2 (C7H5F3S) 6 (DPPF) 2, C7H5F3S represents 2-(trifluoromethyl) thiophenol, and DPPF represents bis (diphenylphosphine) ferrocene, which is simply recorded as Pd2Cu2-2. According to the invention, the Pd2Cu2 nanoclusters are loaded on the carbon nanotubes to obtain the Pd2Cu2-atCNT catalyst, and the Pd2Cu2-atCNT catalyst is used for catalyzing a Suzuki-Miyaura coupling reaction and has excellent catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanomaterials, and particularly relates to a PdCu alloy nanocluster and an application thereof in catalyzing a Suzuki-Miyaura coupling reaction. Background Art

[0002] In the past few decades, metal nanoclusters with extremely small sizes (1-3 nm) have attracted increasing attention due to their precise structures and wide potential applications in a wide range of fields, such as catalysis, medicine, sensing, biotechnology, energy, etc. Among them, the catalytic performance of nanoclusters due to their small size is one of the most attractive and fascinating properties. Bimetallic nanoclusters have attracted much attention recently because they can not only reduce the amount of precious metals used, but also have excellent performance in catalytic reactions. Compared with traditional palladium-based catalysts, the use of PdCu bimetallic atom catalysts can greatly reduce the catalyst cost. In addition, from the perspective of green chemistry, PdCu alloy catalysts are cost-effective options for Suzuki-Miyaura coupling (SMC) reactions.

[0003] The hybrid Pd preparation process using commercial non-precious metals to prepare alloy catalysts has been demonstrated to be an economically feasible and effective route. In particular, copper is an excellent Pd-based alloy catalyst for the synthesis of SMC reactions. On the other hand, supported catalysts can fix the nanoclusters in an ideal dispersed state and further reduce the size of the nanoclusters compared to unsupported catalysts, thereby improving the catalytic performance and durability. The Suzuki-Miyaura reaction is a typical PdCu-catalyzed C-C bond-forming coupling reaction between organic boronic acids and halides, involving the activation of carbon-halogen bonds. These reactions have received extensive attention due to their great industrial potential and wide range of applications. Summary of the invention

[0004] The present invention provides a PdCu alloy nanocluster and its application in catalyzing Suzuki-Miyaura coupling reaction. The PdCu alloy nanocluster of the present invention effectively solves the problem of high usage and economic cost of the noble metal Pd, and the technical problem of difficulty in synthesis and preparation of the supported catalyst.

[0005] The PdCu alloy nanocluster of the present invention is Pd2Cu2(S-Adm)1(DPPM)3, where S-Adm represents adamantane thiol and DPPM represents bis(diphenylphosphinothio)methane, which is abbreviated as Pd2Cu2-1; or is Pd2Cu2(C7H5F3S)6(DPPF)2, where C7H5F3S represents 2-(trifluoromethyl)thiophenol and DPPF represents bis(diphenylphosphinothio)ferrocene, which is abbreviated as Pd2Cu2-2.

[0006] The preparation method of the PdCu alloy nanoclusters of the present invention comprises the following steps: A copper source and a palladium metal salt are dissolved in a mixed solution of dichloromethane and methanol, and a thiol ligand and a diphosphine ligand are added in sequence under stirring at room temperature for initial reaction to obtain a mixed solution, and an aqueous solution of sodium borohydride is added to the obtained mixed solution for a one-pot reduction reaction to obtain an organic phase solution; the organic phase solution is placed at room temperature for crystallization to obtain PdCu alloy nanoclusters.

[0007] Furthermore, the copper source is copper chloride, the palladium metal salt is palladium chloride, the thiol ligand is adamantane thiol, and the bisphosphine ligand is bis(diphenylphosphinothiol) to prepare a PdCu alloy nanocluster Pd2Cu2-1.

[0008] The specific steps are as follows: dissolving copper source cupric chloride in a mixed solution of dichloromethane and methanol, stirring at room temperature, adding a palladium source, and then sequentially adding adamantane thiol and bis(diphenylphosphine)methane for initial reaction to obtain a mixed solution, adding an aqueous solution of sodium borohydride to the mixed solution, performing a one-pot reduction reaction to obtain a crude product, and crystallizing to obtain Pd2Cu2-1 alloy nanoclusters.

[0009] Furthermore, the usage ratio of the copper source, palladium metal salt, thiol ligand, bisphosphine ligand and sodium borohydride is 60 mg:45uL:60mg:50mg:10mL (10mg).

[0010] Furthermore, the copper source is tetrafluoroborate copper tetraacetonitrile, the palladium source is palladium chloride, the thiol ligand is 2-(trifluoromethyl)thiophenol, and the bisphosphine ligand is bisdiphenylphosphinoferrocene, so as to prepare PdCu alloy nanoclusters Pd2Cu2-2.

[0011] The specific steps are as follows: dissolving a copper source, copper tetrafluoroborate tetraacetonitrile, in a mixed solution of dichloromethane and methanol, stirring at room temperature, adding a palladium source, and then sequentially adding 2-(trifluoromethyl)benzenethiol and bis(diphenylphosphinoferrocene) for initial reaction to obtain a mixed solution, adding a methanol solution of sodium borohydride to the mixed solution, performing a one-pot reduction reaction to obtain a crude product, and crystallizing to obtain Pd2Cu2-2 alloy nanoclusters.

[0012] Furthermore, the usage ratio of the copper source, palladium metal salt, thiol ligand, bisphosphine ligand and sodium borohydride is 34 mg:25uL:30uL:50mg:5mL (100mg).

[0013] Furthermore, the reaction time is 8 h.

[0014] Further, the organic phase is purified by using dichloromethane, and the organic phase is crystallized by using dichloromethane / n-hexane (volume ratio is 1:3).

[0015] The invention discloses an application of the PdCu alloy nanoclusters in catalyzing the Suzuki-Miyaura coupling reaction.

[0016] Furthermore, the PdCu alloy nanoclusters were loaded on carbon nanotubes to obtain a Pd2Cu2@CNT catalyst with a loading amount of 1%, which was used to catalyze the Suzuki-Miyaura coupling reaction.

[0017]

[0018] Catalytic reaction conditions: Pd2Cu2@CNT catalyst 50 mg, bromobenzene 1 mmol, phenylboric acid 1.2 mmol, potassium carbonate 2 mmol, solvent 3 ml, reaction temperature 40 ° C. The yield was determined by gas chromatography-mass spectrometry.

[0019] Compared with Pd2Cu2-2@CNT, Pd2Cu2-1@CNT exhibits better catalytic performance in the Suzuki-Miyaura reaction, especially in the activation of C-Br bonds.

[0020] Compared with the prior art, the present invention has the following beneficial effects: The alloy nanoclusters of the present invention are Pd2Cu2(S-Adm)1(DPPM)3 (Pd2Cu2-1 for short) and Pd2Cu2(C7H5F3S)6(DPPF)2 (Pd2Cu2-2 for short). The Pd2Cu2-1 alloy nanocluster is composed of two palladium atoms and two copper atoms, which are then protected and connected by the ligands of S-Adm and DPPM to form a shape similar to a "little turtle". However, the Pd2Cu2-2 nanocluster is also composed of two palladium atoms, two copper atoms and the ligands of C7H5F3S and DPPF to form a linear structure. The two Pd2Cu2 nanoclusters prepared by the present invention are loaded on carbon nanotubes (CNTs) to form catalysts, namely Pd2Cu2-1@CNT and Pd2Cu2-2@CNT. Compared with Pd2Cu2-2@CNT, the Pd2Cu2-1@CNT with Pd-Pd bonds prepared by the present invention has better catalytic performance in the Suzuki-Miyaura reaction, especially in the activation of C-Br bonds, and has a higher contrast, revealing the excellence of Pd-Pd bonds in the Suzuki-Miyaura catalytic reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1The UV-visible absorption spectrum of Pd2Cu2(S-Adm)1(DPPM)3 prepared by the present invention, referred to as Pd2Cu2-1, in CH2Cl2 (a); X-ray photoelectron spectrum (XPS) (c); the UV-visible absorption spectrum of Pd2Cu2(C7H5F3S)6(DPPF)2 prepared by the present invention, referred to as Pd2Cu2-2, in CH2Cl2 (c); X-ray photoelectron spectrum (XPS) (d).

[0022] Figure 2 The overall structural decomposition diagram of Pd2Cu2(S-Adm)1(DPPM)3 and Pd2Cu2(C7H5F3S)6(DPPF)2 prepared by the present invention. Among them: (a) the structure is decomposed into Pd2Cu2, (b) the structure is decomposed into Pd2Cu2(DPPM)3, (c) the structure is decomposed into Pd2Cu2(S-Adm)1(DPPM)3, (d) the structure is decomposed into Pd2Cu2, (e) the structure is decomposed into Pd2Cu2(C7H5F3S)6, (f) the structure is decomposed into Pd2Cu2(C7H5F3S)6(DPPF)2. Color labels: dark green represents Pd (palladium), orange represents Cu (copper), dark yellow represents Fe (iron), red represents S (sulfur), purple represents P (phosphorus), dark red represents F (fluorine), green represents Cl (chlorine), and H atoms are omitted.

[0023] Figure 3 The structural differences between Pd2Cu2(S-Adm)1(DPPM)3 (a) and Pd2Cu2(C7H5F3S)6(DPPF)2 (b) prepared in the present invention are highlighted.

[0024] Figure 4 (a) Line graph of the conversion rate and yield of bromobenzene and biphenyl after Suzuki-Miyaura reaction of Pd2Cu2-1@CNT prepared by the present invention (X=Br); (b) catalytic performance of CNT, Pd2Cu2-1@CNT, Pd2Cu2-2@CNT, DPPM, DPPF, C7H5F3S and S-Adm after Suzuki-Miyaura reaction; (c) comparison of the conversion rates of Pd2Cu2-1@CNT and Pd2Cu2-2@CNT after Suzuki-Miyaura reaction (X=Cl, Br, I); (d) cyclic test of Pd2Cu2-1@CNT in Suzuki-Miyaura reaction (X=Br).

[0025] Figure 5 Bond length diagram of Pd2Cu2-1 prepared in accordance with the present invention.

[0026] Figure 6Bond length diagram of Pd2Cu2-2 prepared in accordance with the present invention.

[0027] Figure 7 This is the XRD pattern of Pd2Cu2-1@CNT prepared in the present invention.

[0028] Figure 8 This is the XRD pattern of Pd2Cu2-2@CNT prepared in the present invention.

[0029] Fig. 9 TEM image of Pd2Cu2-1@CNT prepared according to the present invention.

[0030] Fig.10 TEM image of Pd2Cu2-2@CNT prepared according to the present invention. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention. The following test methods and detection methods, unless otherwise specified, are conventional methods; the reagents and raw materials, unless otherwise specified, are commercially available.

[0032] The effects are described below in conjunction with the specific test process and preparation method.

[0033] Experimental drugs: palladium chloride (PdCl2), copper chloride (CuCl2), copper tetrafluoroborate tetraacetonitrile (Cu(CH3CN)4·BF4), bis(diphenyl)ferrocene (Dppf), bis(diphenylphosphine)methane (Dppm), 1-adamantanethiol (HS-Adm), 2-(trifluoromethyl)thiophenol (C7H5F3S), and sodium borohydride (NaBH4) were purchased from Shanghai MacLean Biochemical Co., Ltd. Solvents including dichloromethane (DCM, HPLC grade), methanol (MeOH, HPLC grade), and n-hexane (n-Hex, HPLC grade) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. The ultrapure water used in this study was purified on a micropore system. Embodiment 1:

[0034] The preparation method of Pd2Cu2-1 alloy nanoclusters comprises the following steps: First, 60 mg of copper chloride was dissolved in a mixture of 5 ml of methanol and 15 ml of dichloromethane (volume ratio v / v = 1 / 3). Then, 45 ul of the prepared palladium chloride solution was slowly added dropwise during stirring. Subsequently, 50 mg of bis(diphenylphosphine)methane was introduced into the flask. Subsequently, 60 mg of 1-adamantanethiol was added to the mixture and stirred for another 25 minutes to allow for sufficient interaction and initial reaction between the ligand and the metal. After this period of time, 10 mg of NaBH4 dissolved in 1 ml of water was added for further reaction and formation of nanoclusters. The reaction mixture immediately turned into a brown solution. Over the course of 8 hours, it is noteworthy that the color of the solution changed from brown to reddish brown and finally to an orange-red state, indicating the formation of the desired nanoclusters. The next step was to extract the reaction mixture with CH2Cl2 to separate the product from the reaction solvent and byproducts. The purified CH2Cl2 organic phase was collected and crystallized using dichloromethane / n-hexane at room temperature. After 5 days, red rod-shaped single crystals were formed to obtain Pd2Cu2-1 alloy nanoclusters, namely Pd2Cu2(S-Adm)1(DPPM)3. Embodiment 2:

[0035] The preparation method of Pd2Cu2-2 alloy nanoclusters comprises the following steps: First, 34 mg of tetraacetonitrile copper tetrafluoroborate was dissolved in a mixture of 10 ml methanol and 10 ml dichloromethane (volume ratio v / v=1 / 1). Then, 25 ul of the prepared palladium chloride solution was slowly added dropwise during the same stirring process. Subsequently, 50 mg of bis(diphenylphosphino)ferrocene and 30 ul of 2-(trifluoromethyl)thiophenol were added to the solution, and interestingly, the solution immediately showed a deep red color. Stirring was continued for another 20 minutes to allow sufficient interaction and preliminary reaction between the ligand and the metal. Then 100 mg of NaBH4 dissolved in 5 mL of methanol solution was added to the reactor. The color of the solution changed to dark brown within 5 minutes. It is worth mentioning that the color of the solution changed from deep red to orange, indicating the formation of the desired nanoclusters. After 8 hours of work-up reaction, the reaction mixture was extracted with CH2Cl2 to separate the product from the reaction solvent and by-products. The purified CH2Cl2 organic phase was collected and crystallized using dichloromethane / n-hexane at room temperature. After 15 days, black fast-shaped single crystals were formed to obtain Pd2Cu2-2 alloy nanoclusters, namely Pd2Cu2(C7H5F3S)6(DPPF) 2。

[0036] The properties of the Pd2Cu2(S-Adm)1(DPPM)3 alloy nanoclusters and Pd2Cu2(C7H5F3S)6(DPPF)2 alloy nanoclusters prepared above were tested. The specific process and results are as follows: 1. Test methods 1. The UV-visible absorption spectra of all nanoclusters were recorded using Agilent 8453. The samples were dissolved in dichloromethane, and the background correction was performed using a dichloromethane blank sample.

[0037] 2. X-ray photoelectron spectroscopy (XPS) measurements were performed on a thermal scale ESCALAB 250 equipped with a monochromatic aluminum Kα (1486.8 Ev) 150 W X-ray source, 0.5 mm circular spot size and a flow ejector.

[0038] 3. F200 field emission transmission electron microscope (TEM F200) test was conducted on JEM-F200. The sample was dissolved in ethanol solution and dropped on a molybdenum mesh for testing.

[0039] 4. Single-crystal X-ray diffraction data were collected on a Bruker Smart APEX II CCD diffractometer at 120 K using graphite-monochromatized Cu Kα radiation (λ = 1.54186 Å).

[0040] 5. X-ray diffractometer (XRD) testing uses a high-resolution θ / θ closed-loop goniometer drive system, a crossed beam optical system (CBO) and a 9.0 kW rotating cathode X-ray generator.

[0041] 6. Gas chromatograph (GC-MS) test was conducted using GC-2010Pro.

[0042] (II) Test results 1. Synthesis and characterization of Pd2Cu2-1 and Pd2Cu2-2 nanoclusters Pd2Cu2-1 and Pd2Cu2-2 nanoclusters were synthesized using a one-pot method, as described in the preparation methods of Examples 1 and 2. The overall structures of the two alloy nanoclusters are shown in Figure 2 As shown in Figures c and f.

[0043] Single crystal X-ray crystallography determined the crystal structures of Pd2Cu2-1 and Pd2Cu2-2, both of which adopt the P-1 space group, as shown in Tables 1 and 2. The crystal structure of Pd2Cu2-1 consists of 2 Cu atoms, 2 Pd atoms, 2 Cl atoms, 6 P atoms and 1 S atom. The overall structure of Pd2Cu2(S-Adm)1(DPPM)3 is shown in Figure 2 c, which is protected and connected by adamantanethiol ligand and bis(diphenylphosphinothio)methane. Structural analysis shows that the two Cu atoms and the two Cl atoms form a distorted Cu-Cl-Cu-Cl tetragon with a Pd-Pd bond on top. Figure 2a, The distances between the PdCu metal atoms are 3.074 Å and 3.090 Å, respectively, which are beyond the usual Pd-Cu bond formation range, indicated by the dashed lines. Interestingly, the PdCu metal atoms rely on Figure 2 b) The bis(diphenylphosphinothioic acid) is connected. Subsequently, the S atom in adamantane thiol forms a triangle with two Pd atoms, which, as the head of Pd2Cu2-1, can be seen as a "turtle" shape ( Figure 2 c). One of its characteristics is that a metallic bond Pd-Pd bond is formed with a bond length of 2.638 Å. In addition, the rest is connected to S atoms or P atoms. The structure of Pd2Cu2-2 is composed of 2 Cu atoms, 2 Pd atoms, 2 Fe atoms, 6 S atoms, 18 F atoms and 4 P atoms. The overall structure of Pd2Cu2(C7H5F3S)6(DPPF)2 is as follows Figure 2 f, co-protected and linked by 2-(trifluoromethyl)thiophenol and bis(diphenylphosphinoferrocene). Figure 2 e four metal atoms are arranged linearly with a twisted angle. The distance between every two metal atoms is approximately equal to 3.18 Å, resulting in the inability to form metallic bonds, which paves the way for the further formation of three twisted tetragons with S atoms in the six thiol ligands ( Figure 2 e). Two bis(diphenylphosphinoferrocene) are connected on both sides of the structure to form Figure 2 Pd2Cu2-2 in f.

[0044] The UV-visible spectrum shows three prominent peaks centered at 362 nm and 455 nm and a weak peak at 309 nm for Pd2Cu2-1 dissolved in dichloromethane. Figure 1 a, the inset on the upper right shows the Pd2Cu2-1 crystal under the microscope, which appears as a red rod. As for Pd2Cu2-2, the UV-visible spectrum of pure Pd2Cu2-2 crystal dissolved in dichloromethane shows a significant peak at 388 nm and a weak peak at 306 nm, as shown in Figure 1 b.

[0045] X-ray photoelectron spectroscopy confirmed the presence of Pd, Cu, S, P, Cl, Figure 1 X-ray photoelectron spectroscopy confirmed the presence of Pd, Cu, Fe, S, P, and F in Pd2Cu2-2. Figure 1 c. And Figure 5 and 6 As shown, Pd shows a valence state of +2 at the center of both Pd2Cu2-1 and Pd2Cu2-2, and Cu shows a valence state of +1 at the center of both Pd2Cu2-1 and Pd2Cu2-2.

[0046]

[0047]

[0048] 2. Characterization of catalytic performance of Pd2Cu2-1@CNT and Pd2Cu2-2@CNT X-ray diffractometer (XRD) confirmed that Pd2Cu2-1 and Pd2Cu2-2 were respectively loaded on carbon nanotubes and were consistent with blank carbon nanotubes after organic catalytic reaction, with almost no change, indicating that there was no aggregation before and after the reaction.

[0049] F200 field emission transmission electron microscopy (TEM F200) detected that there was no aggregation in Pd2Cu2-1@CNT and Pd2Cu2-2@CNT, and they had good morphology.

[0050] 3. Comparative study on the catalytic performance of Pd2Cu2-1@CNT and Pd2Cu2-2@CNT The catalytic performance of Pd2Cu2-1@CNT was investigated in methanol solvent at 40 °C by Suzuki-Miyaura reaction. The conversion of bromobenzene on Pd2Cu2-1@CNT and the selectivity for biphenyl products are shown in Figure 2. Figure 4 a. After 4 h, the conversion of bromobenzene reached 74.02%, and the selectivity of biphenyl remained almost 100%. Therefore, the reaction has high selectivity and good conversion. It is worth noting that when the reaction time was extended to 12 h, the selectivity of biphenyl remained stable at about 100%, indicating that Pd2Cu2-1@CNT hardly catalyzed other bromobenzene products under this condition, showing good selectivity for biphenyl. As time went on, its conversion almost remained balanced, indicating that 4 h was the optimal and mildest reaction time. However, under the same conditions, a trace amount of bromobenzene conversion of 2% was detected in blank carbon nanotubes (CNTs) within 4 h, indicating that the Pd site played the role of a catalytic center in this reaction. In order to investigate the differences in properties between Pd2Cu2-1@CNT and Pd2Cu2-2@CNT and control the halogenated benzene due to different substituents, the carbon-carbon coupling reaction between bromobenzene and phenylboronate was used as a model reaction. Therefore, we compared the catalytic activity of iodobenzene and chlorobenzene with different substituents on bromobenzene. For Pd2Cu2-1@CNT, the conversion of iodobenzene reached 70%, and the selectivity of biphenyl remained at 100%. Because the bond energy of C-Cl bond is higher. And it is more difficult to activate. Therefore, under the same conditions, the conversion of chlorobenzene reached 10%. Subsequently, in order to better reveal the superiority and catalytic activity of Pd2Cu2-1@CNT, we drew a bar graph to more intuitively show the difference between the two, such as Figure 4c. It can be seen that iodobenzene and chlorobenzene have almost no catalytic activity on Pd2Cu2-2@CNT. As expected, under the combined effect of the synergistic effect of Pd-Pd bonds and the strong metal-support interaction, Pd2Cu2-1@CNT exhibited superior catalytic activity and selectivity to Pd2Cu2-2@CNT catalyst in the Suzuki−Miyaura reaction. Next, the recyclability experiment of Pd2Cu2-1@CNT was studied to evaluate the stability of the catalyst for the Suzuki-Miyaura reaction under the same mild conditions. The results of Pd2Cu2-1@CNT are shown in Figure 2. Figure 4 d. Unfortunately, the stability was only maintained for three cycles during the reaction, but after three cycles, the selectivity for the biphenyl product exceeded 90%.

[0051] In summary, two small-sized Pd2Cu2 nanoclusters Pd2Cu2(S-Adm)1(DPPM)3 (Pd2Cu2-1 for short) and Pd2Cu2(C7H5F3S)6(DPPF)2 (Pd2Cu2-2 for short) were synthesized by a one-pot method and well confirmed by single crystal X-ray crystallography (SCXRD) and X-ray photoelectron spectroscopy (XPS). The single crystal X-ray crystallography (SCXRD) data showed that the Pd2Cu2-1 structure was considered to be a "turtle" shape, while the Pd2Cu2-2 structure was considered to be a linear arrangement. Among them, the most interesting and critical point is whether there are Pd-Pd bonds in the two nanoclusters. Compared with Pd2Cu2-2@CNT, Pd2Cu2-1@CNT with Pd-Pd bonds showed better catalytic performance in Suzuki-Miyaura reaction, especially in C-Br bond activation. Under the conditions of Pd2Cu2-1@CNT, the conversion of bromobenzene reached 74.02%, and the selectivity of biphenyl remained almost 100%. Considering green chemistry and cost-effectiveness, Pd2Cu2-1@CNT shows great potential for industrial application, laying a foundation for the subsequent development of small-sized PdCu bimetallic nanoclusters.

[0052] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A PdCu alloy nanocluster, characterized in that: The chemical formula of the PdCu alloy nanocluster is Pd2Cu2(S-Adm)1(DPPM)3, S-Adm represents adamantanethiol, DPPM represents bis(diphenylphosphinothio)methane, and is abbreviated as Pd2Cu2-1; Alternatively, the chemical formula of the PdCu alloy nanocluster is Pd2Cu2(C7H5F3S)6(DPPF)2, where C7H5F3S represents 2-(trifluoromethyl)thiophenol and DPPF represents bis(diphenylphosphinoferrocene), which is abbreviated as Pd2Cu2-2.

2. The method for preparing the PdCu alloy nanoclusters according to claim 1, characterized in that The steps include: Dissolving a copper source and a palladium metal salt in a mixed solution of dichloromethane and methanol, adding a thiol ligand and a bisphosphine ligand in sequence under stirring at room temperature for a primary reaction to obtain a mixed solution, adding an aqueous solution of sodium borohydride to the obtained mixed solution, performing a one-pot reduction reaction to obtain an organic phase solution; The organic phase solution is placed at room temperature for crystallization to obtain PdCu alloy nanoclusters.

3. The preparation method according to claim 2, characterized in that: The copper source is copper chloride, the palladium metal salt is palladium chloride, the thiol ligand is adamantane thiol, and the bisphosphine ligand is bis(diphenylphosphinothiol), and a PdCu alloy nanocluster Pd2Cu2-1 is prepared.

4. The preparation method according to claim 2, characterized in that: The copper source is tetraacetonitrile copper tetrafluoroborate, the palladium source is palladium chloride, the thiol ligand is 2-(trifluoromethyl)thiophenol, and the bisphosphine ligand is bisdiphenylphosphinoferrocene, and a PdCu alloy nanocluster Pd2Cu2-2 is prepared.

5. Use of the PdCu alloy nanoclusters according to claim 1 in catalyzing Suzuki-Miyaura coupling reaction.

6. The use according to claim 5, characterized in that: The PdCu alloy nanoclusters are loaded on carbon nanotubes to obtain Pd2Cu2@CNT catalysts, which are used to catalyze Suzuki-Miyaura coupling reactions.

7. The use according to claim 6, characterized in that: Using bromobenzene and phenylboronic acid as reaction substrates, Suzuki-Miyaura coupling reaction was carried out in the presence of Pd2Cu2@CNT catalyst and potassium carbonate to obtain biphenyl product.

Citation Information

Patent Citations

  • Alloy metal nanocluster and preparation method and application thereof

    CN118165042A